Lagrangian Vortex Computations of a Four Tidal Turbine Array: An Example Based on the NEPTHYD Layout in the Alderney Race - Michael Togneri (Energies, 2021)
This study investigates the wake interaction of four full-scale three-bladed tidal turbines with different ambient turbulence conditions, in straight and yawed flows. A three-dimensional unsteady Lagrangian Vortex Blob software is used for the numerical simulations of the turbines’ wakes. In order to model the ambient turbulence in the Lagrangian Vortex Method formalism, a Synthetic Eddy Method is used. With this method, turbulent structures are added in the computational domain to generate a velocity field which statistically reproduces any ambient turbulence intensity and integral length scale. The influence of the size of the structures and their density (within the study volume) on the wake of a single turbine is studied. Good agreement is obtained between numerical and experimental results for a high turbulence intensity but too many structures can increase the numerical dissipation and reduce the wake extension. Numerical simulations of the four turbine array with the layout initially proposed for the NEPTHYD pilot farm are then presented. Two ambient turbulence intensities encountered in the Alderney Race and two integral length scales are tested with a straight flow. Finally, the wakes obtained for yawed flows with different angles are presented, highlighting turbine interactions.